Life adjustment after surgical treatment for temporal lobe epilepsy - Salgado,Priscila Camile Barioni (2009)
OBJECTIVE: The purpose of this study was to evaluate the patients' life adjustment after epilepsy surgery, through instruments of quality of life (QoL), anxiety, depression, preoperative expectations and postoperative life changing. METHODS: Thirty-six adults who underwent temporal lobe epilepsy surgery were interviewed before surgery, and 6 and 12 months after surgery. RESULTS: For all patients, epilepsy surgery gave rise to an evolving process of postoperative adjustment, what means that they were satisfied with surgery results, and that their expectations were reached. The improvement was seen in their QoL (p=0.004), anxiety (p=0.019) and depression (p=0.001), which was associated to their perception of positive life changing. The inexistence of depressive and anxiety symptoms and the good QoL after surgery predicted the perception of positive life changing. This study could predict a total of 56.5% of aspects involved in the perception of positive life changing after epilepsy surgery, what seems that other variables may be involved in this process. The patients' status before surgery (expectations, QoL, anxiety, depression and seizures frequency) did not predict the life satisfaction after surgery, what means that when patients evaluate their actual lives they do it looking for daily aspects and do not tend to compare to their lives before surgery. CONCLUSION: The findings of the present study have implications for the evaluation of life adjustment postsurgery, calling attention to measures of preoperative expectations, anxiety, depression and QoL. The strength of these contributions highlights the importance of registering the patients' feelings and opinions during the presurgical evaluation and may help the health providers to understand the aspects necessary to improve the patients' quality of life.